1977
DOI: 10.1002/art.1780200208
|View full text |Cite
|
Sign up to set email alerts
|

Azathioprine in early rheumatoid arthritis

Abstract: This study compares the effect of azathioprine with those of gold and chloroquine in early (Class 11) rheumatoid arthritis (RA). Thirty-three similar patients with classic or definite R A of less than 5 years duration were randomly entered, 11 into each drug group. Assessment of standard clinical and laboratory measures at 12 and 24 weeks showed significant improvement in all three groups. In genergl, all three drugs were effective antirheumatic agents with low toxicity. However, because of serious potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

1982
1982
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 18 publications
2
19
2
Order By: Relevance
“…This was also reflected in part by the non-significant improvement in ESR (Fig. 2), and supports the haematological data from previous comparative studies with o-penicillamine [3] and gold [4]. The non-significant fall in ESR occurred despite highly significant improvement in CRP and plasma viscosity (p < 0.01), a phenomenon also seen during hydroxychloroquine therapy [12].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This was also reflected in part by the non-significant improvement in ESR (Fig. 2), and supports the haematological data from previous comparative studies with o-penicillamine [3] and gold [4]. The non-significant fall in ESR occurred despite highly significant improvement in CRP and plasma viscosity (p < 0.01), a phenomenon also seen during hydroxychloroquine therapy [12].…”
Section: Discussionsupporting
confidence: 89%
“…Eleven patients were strongly seropositive, but suppression of rheumatoid factor as measured by SCAT only occurred in one patient. This is contrary to a previous report which demonstrated a highly significant improvement in latex titre [4]. In view of the lack of improvement in rheumatoid factor, the increase in serum histidine was perhaps surprising considering the possible relationship between histidine and rheumatoid factor [221.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…Previous controlled studies also have demonstrated the effectiveness of hydroxychloroquine, although over shorter periods of followup (12)(13)(14). Althuugh hydroxychloroquine does not seem as effective as D-penicillamine in our study, about 50% of patients remain improved over 2 years, and half of those are markedly improved.…”
Section: Discussioncontrasting
confidence: 53%
“…The efficacy of hydroxychloroquine is similar to that reported for other disease modifying antirheumatic drugs, with 60-80% of adult rheumatoid arthritics improving with hydroxychloroquine therapy (Mainland & Sutcliffe, 1962;Hamilton & Scott, 1962;Kersley & Palin, 1959;Adams et al, 1983;Dwosh et al, 1977). However, the main reasons for discontinuing therapy differ between the slow acting antirheumatic drugs (Paulus, 1982).…”
Section: Introductionsupporting
confidence: 57%